ANALISIS PENGARUH PUTUSAN HAKIM KONSTITUSI TERHADAP PUTUSAN MAHKAMAH KONSTITUSI No. 90/PUU-XXI/2023 - Anwar, Khoirul (HUKMY : Jurnal Hukum, 2024)
The constitution states that the Indonesian state is a rule of law enforced by the government under the mandate of paragraph 4 of the preamble to the 1945 NRI constitution, which states that its duty is to protect the entire Indonesian people and the bloodshed of all. Indonesia. manifestation of the fifth commandment and "Social justice for all Indonesians" and ". Which establishes the Constitutional Court as the supervisor of the Constitution and also as the exerciser of judicial power. If there is a law whose content contradicts the Constitution. , the court can cancel the existence of the law or in whole or in part declaring that it the decision of the Constitutional Court does not have binding legal force and the decision is definitive and binding in nature. In this study, the author focuses more on the nature of the decision of the Constitutional Court, which differs from other decisions. The purpose of this study is to find ways in which the decision of the Constitutional Court can be studied in a similar way to other decisions. The purpose of this study is to find ways in which the decision of the Constitutional Court can be studied in a similar way to other decisions. Standard, legal and with the help of a literature review.